2013
DOI: 10.1136/bmjqs-2013-002357
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a clinical pharmacist-led training programme on intravenous medication errors: a controlled before and after study

Abstract: The pharmacist-led training programme was effective, but the error rate remained relatively high. Further quality improvement strategies are needed, including changes to the working environment and promotion of a safety culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 35 publications
(31 reference statements)
0
68
0
3
Order By: Relevance
“…28 Studies demonstrated that nurse education is one type of intervention to reduce MEs. 18,30,31 Providing nurse training and information about the most frequent errors, "uniform mixing", "labeling", and "infusion rate", in our study may help to reduce these error types. In a study by Chua et al, an intervention between two observation periods showed a reduction in the administration errors from 44.3% to 28.6%.…”
Section: Discussionmentioning
confidence: 99%
“…28 Studies demonstrated that nurse education is one type of intervention to reduce MEs. 18,30,31 Providing nurse training and information about the most frequent errors, "uniform mixing", "labeling", and "infusion rate", in our study may help to reduce these error types. In a study by Chua et al, an intervention between two observation periods showed a reduction in the administration errors from 44.3% to 28.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of the wrong drug was a cause of error reported by the working group. In a recent study about intravenous medication administration errors in hospital, the prevalence of wrong drug was 0.4% . Scanning drugs at the time of storage in the unit cabinet would secure this critical step.…”
Section: Resultsmentioning
confidence: 99%
“…While our intervention study was primarily targeted at medicine in tablet form, previous studies have found intravenous therapy to be associated with a higher prevalence of medication errors compared with orally administered medications 19 20. It would be relevant to include intravenous medicine in future technological endeavours to reduce medication errors.…”
Section: Discussionmentioning
confidence: 99%